The Role of Islamic Banking Through Green Investment in Increasing Economic Growth in Indonesia - Ackil Maulana Marwan; Muhammad Aqim Adlan; Risdiana Himmati (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This study aims to explore how much potential Islamic banks in Indonesia have in contributing through environmental improvement. Methodology: This research uses the literature review method which is then supported by descriptive analysis. Research Findings: The research shows that Indonesia has great potential regarding green economic opportunities, which in turn can contribute greatly to national economic growth. Theoretical Contribution : The increasing trend in the green economy index in Indonesia and its correlation with progressive economic indicators contribute theoretically by suggesting that a green economy can coexist with economic growth Research limitation and implication: This research has limitations, one of which is only finding out how the role of Islamic banking in Indonesia in participating in protecting the environment. as for the factors discussed in this study are also limited, namely only looking at the green investment or green financing of Islamic banks.